Community Perceptions of Urban Forest Functions in Metropolitan Areas: Evidence from Dukuh City Forest, Jakarta - Firdaus Firdaus; Nur Fazreen Zainal; Juraj Nič (Journal of Academic Biology and Biology Education, 2025)
Purpose of the study: This study aims to evaluate community perceptions regarding the ecological, social, landscape, and aesthetic functions of Dukuh City Forest as an urban green space in a densely populated metropolitan area of Jakarta, Indonesia, and to examine its contribution to sustainable urban environmental management. Methodology: This study employed a convergent mixed-methods approach integrating quantitative and qualitative techniques. Data were collected through participatory observation, documentation, semi-structured interviews, and Likert-scale questionnaires distributed to 35 respondents selected using random sampling techniques. Quantitative data were analyzed using descriptive statistical and percentage scoring methods, while qualitative data were analyzed thematically and integrated through triangulation. Main Findings: The findings showed that public perception of Dukuh City Forest functions was categorized as good, with an overall score of 68.91%. The ecological function received the highest score (82.94%), indicating strong public awareness of environmental benefits such as improving air quality, reducing urban heat, and increasing water absorption capacity. In contrast, aesthetic and recreational functions received the lowest scores due to limited public utilization, insufficient environmental outreach, and persistent social stigma associated with the area’s previous function as a public cemetery. Limited communication between authorities and communities also affected public participation in urban forest management. Novelty/Originality of this study: This study strengthens the socio-ecological urban forest approach by integrating ecological and social perspectives in evaluating urban forest functions and linking urban forest management with Sustainable Development Goals (SDGs)-based sustainable urban development.